Efforts by Educators to Prevent Bullying in Islamic Boarding Schools Princess Walisongo - zizah Asmaul Fauzi (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The role of Islamic education is very important in shaping the character and ethics of Muslim individuals. The aim of an Islamic educational environment, such as Islamic boarding schools, is to create a friendly and peaceful atmosphere. Madrasas must be able to achieve the highest goal of education, namely truly developing individuals into humane and compassionate human beings. Islamic boarding schools can also be a social factor that can influence the lives and experiences of students. Bullying or harassment is one of the social problems that is of concern in the realm of Islamic education. Such as physical, verbal or emotional harm, as well as intimidation or degradation of the victim. The aims of this research are as follows: 1) Causes of bullying behavior at the Putri Walingo Islamic boarding school, 2) Efforts of teaching staff in preventing bullying at the Putri Walingo Islamic boarding school, 3) Factors Supporters and inhibitors of Islamic boarding schools in efforts to prevent bullying . The results of the research show that 1) the causes of bullying behavior at the Putri Walisongo Cukir Jombang Islamic boarding school are: a) the influence of upbringing from the family, b) the school environment, c) interactions from peers. 2) the efforts of educational staff in preventing bullying at the Putri Walisongo Cukir Jombang Islamic boarding school include : a) reducing the gap between new students and old students through team activities: b) forming a committee to prevent bullying c) utilizing Islamic boarding school resources d) providing counseling services e) forming peer support groups to overcome bullying. factor Supporters and inhibitors of Islamic boarding schools in efforts to prevent bullying . 1) inhibiting factors: a) low understanding of bullying, b) the role of parents is lacking. 2) Supporting factors: a) effective communication between parents and students, b) selective friends, c) positive attitude, d) self-confidence.